1994
DOI: 10.1073/pnas.91.17.8052
|View full text |Cite
|
Sign up to set email alerts
|

SB 209670, a rationally designed potent nonpeptide endothelin receptor antagonist.

Abstract: An extremely potent and highly specific nonpeptide, subnanomolar endothelin (ET) receptor antagnist, SB 209670, has been synthesized and characterized. SB 209670, which was rationally designed using conformational models of ET-1, selectively inhibits binding of 12SI-labeled ET- Endothelin-1 (ET-1) is a potent endothelium-derived vasoconstrictor peptide (1). ET-1 has pronounced effects on the cardiovascular system and, in particular, on the coronary, renal, and cerebral circulatory beds. Elevated or abnormal bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(67 citation statements)
references
References 27 publications
0
67
0
Order By: Relevance
“…Nonselective receptor antagonists such as SB209670 22 kg. This is because the reduction of the infarcted area of 15.…”
Section: Discussionmentioning
confidence: 99%
“…Nonselective receptor antagonists such as SB209670 22 kg. This is because the reduction of the infarcted area of 15.…”
Section: Discussionmentioning
confidence: 99%
“…SAR studies on peptide and non-peptide small molecule antagonists have pointed to the importance of a juxtaposition of an acidic group (presumably Asp 18 in the native endothelin) and at least one aromatic group (in native ET this would likely be Trp 21 ). Thus, it was postulated that these types of side chains should be in 382 similar relative positions in both the small molecule and in the native peptide [34]. In BQ123 the corresponding groups would appear to be o-Asp The overlay studies reported here would suggest that the endothelin A receptor binding site has a geometry that would accommodate the tryptophan side chain as well as a closely juxtaposed carboxylate from the aspartic acid sidechain, but that the residues on the opposite side of the molecule (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest in this connection, SB209670 strongly attenuated neointima formation following rat carotid artery balloon angioplasty (127,233). In angioplasty-induced neointima in rats, expressions of the mRNAs of endothelin-1, endothelin-3, ECE-1, ETA and ETB receptor were found to be increased (234).…”
Section: V-5 Vascular Thickeningmentioning
confidence: 99%
“…Although the effects of peptide antagonists for endothelin receptors in spontaneously hypertensive rats (SHR) are currently controversial (147)(148)(149), the nonpeptide antagonist SB209670 has recently been shown to exert significant and long-lasting hypotensive actions following intraduodenal administration in this particular model of hypertension (127). The nonpeptide antagonists have been demonstrated to be effective in lowering blood pressure in various animal models of hypertension; e.g., sodium-depletion-induced hypertension in squirrel monkeys (124), renal hypertension in dogs (150) and mouse renin transgenic ((mRen-2) 27) hypertensive rats (151).…”
Section: V-1 Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation